Medication adherence in chronic condtions : a scoping review of barriers, facilitators and interventions - Konstantinou, Pinelopi; Kassianos, Angelos P.; Georgiou, Giorgos; Panayides, Andreas; Papageorgiou, Alexia; Almas, Ioannis; Wozniak, Greta E.; Karekla, Maria (My University, 2021)
As the cancer survivor population in the US continues to increase, diminished health care provider capacity will result in cancer survivors bearing more responsibility for obtaining health-related information. Pervasive internet and digital technology use has dramatically increased the availability and accessibility of online health information targeted to cancer survivors. Much needs to be learned about how survivors seek out and engage with this information, and whether these patterns vary by personal characteristics and cancer type. This study therefore examined the information-seeking behaviors and perceptions of cancer survivors during a self-guided online search task.